Development of a Comprehensive Osteochondral Allograft MRI Scoring System (OCAMRISS) With Histopathologic, Micro–Computed Tomography, and Biomechanical Validation. (January 2014) - Chang, Eric Y.; Pallante-Kichura, Andrea L.; Bae, Won C.; Du, Jiang; Statum, Sheronda; Wolfson, Tanya; Gamst, Anthony C.; Cory, Esther; Amiel, David; Bugbee, William D.; Sah, Robert L.; Chung, Christine B.
Objective : To describe and apply a semiquantitative MRI scoring system for multifeature analysis of cartilage defect repair in the knee by osteochondral allografts and to correlate this scoring system with histopathologic, micro–computed tomography (µCT), and biomechanical reference standards using a goat repair model. Design : Fourteen adult goats had 2 osteochondral allografts implanted into each knee: one in the medial femoral condyle and one in the lateral trochlea. At 12 months, goats were euthanized and MRI was performed. Two blinded radiologists independently rated 9 primary features for each graft, including cartilage signal, fill, edge integration, surface congruity, calcified cartilage integrity, subchondral bone plate congruity, subchondral bone marrow signal, osseous integration, and presence of cystic changes. Four ancillary features of the joint were also evaluated, including opposing cartilage, meniscal tears, synovitis, and fat-pad scarring. Comparison was made with histologic and µCT reference standards as well as biomechanical measures. Interobserver agreement and agreement with reference standards was assessed. Cohen's κ, Spearman's correlation, and Kruskal-Wallis tests were used as appropriate. Results : There was substantial agreement (κ > 0.6, P < 0.001) for each MRI feature and with comparison against reference standards, except for cartilage edge integration (κ = 0.6). There was a strong positive correlation between MRI and reference standard scores (ρ = 0.86, P < 0.01). Osteochondral allograft MRI scoring system was sensitive to differences in outcomes between the types of allografts. Conclusions : We have described a comprehensive MRI scoring system for osteochondral allografts and have validated this scoring system with histopathologic and µCT reference standards as well as biomechanical indentation testing.